2010
DOI: 10.1159/000319923
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Severity of Cerebral Small Vessel Disease, Pulsatility of Cerebral Arteries, and Brachial Ankle Pulse Wave Velocity in Patients with Lacunar Infarction

Abstract: Background/Aims: Stiff arteries cause high pulse pressure and flow to be transmitted to distal organs during systole, damaging the cerebral microvasculatures. We investigated the association between the severity of cerebral small vessel disease (CSVD), the pulsatility of cerebral arteries, and the stiffness of large arteries in patients with lacunar infarction (LI). Methods: Subjects included 120 patients with LIs, who underwent MRI, transcranial Doppler ultrasonography, and brachial ankle pulse wave velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…However, these variables may not account for changes in pulsatile hemodynamics associated with aging and hypertension. As the impact of arterial stiffness on the brain is realized (24,51), the importance of understanding pulsatile regulatory mechanisms of cerebral hemodynamics will become essential. CrCP and RAP are sensitive to both pulsatile and mean characteristics of the pressure wave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these variables may not account for changes in pulsatile hemodynamics associated with aging and hypertension. As the impact of arterial stiffness on the brain is realized (24,51), the importance of understanding pulsatile regulatory mechanisms of cerebral hemodynamics will become essential. CrCP and RAP are sensitive to both pulsatile and mean characteristics of the pressure wave.…”
Section: Discussionmentioning
confidence: 99%
“…Despite similar posture-induced changes in mean pressure, PP is reduced in young adults and maintained in older adults during standing (29). Further, within-beat pulsatile characteristics are enhanced by arterial stiffening common to aging and hypertension (24,51), yet their influence on CA has not been thoroughly examined. A comparison of CA in hypertension, through transfer function analysis (TFA) at the cardiac frequency (ϳ1.0 Hz), found that hypertensive older adults retained autoregulatory function (45); however, the TFA approach still relies on dynamic fluctuations of mean pressure and velocity.…”
mentioning
confidence: 99%
“…Cerebral autoregulation (CA) maintains a relatively constant CBF, over a wide range of precerebral arterial pressure [2]. With aging, the cardiovascular system undergoes numerous changes, including an increase in the systolic pressure, a decrease in the arterial compliance and changes in the cerebrovascular hemodynamic [3]. The loss of CA may be an important risk factor for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the development of diabetic microangiopathy, including microalbuminuria (12), renal dysfunction (13,14), retinopathy (15), neuropathy (16,17), and evidence of macroangiopathy (18)(19)(20)(21), is individually associated with the progression of arterial stiffness. These pathological complexities in subjects with diabetes might necessitate a review of adequate baPWV thresholds that splice the risks of mortality and morbidity.…”
mentioning
confidence: 99%